PERUBAHAN SIFAT KIMIA ANDISOL AKIBAT PEMBERIAN SILIKAT DAN PUPUK P UNTUK MENINGKATKAN PRODUKSI KENTANG (Solanum tuberosum L.) - Ina Santa Santa Monica Br Sembiring; Mukhlis Mukhlis; Bintang Sitorus (Universitas Sumatera Utara, 2013)
Field research was conducted applied Agrosil as silicate material and Phosphorus fertilizer forpotato plant to determine the changes of chemical characteristics of Andisols and yield of potato.This research used Factorial Blocky Randomized Design with treatment Si dosage 0 kg SiO2/ha(S0), 750 kg SiO2/ha (S1), 1500 kg SiO2/ha (S2), 2250 kg SiO2/ha (S3), and P fertilizer dosage 0 kgP2O5/ha (P0), 90 kg P2O5/ha (P1), 180 kg P2O5/ha (P2), 270 kg P2O5/ha (P3), so there are sixteencombination and three blocks, so there are fourty eight units treatments. This result showed thatapplied Agrosil could increase soil pH, SiO2 available and decrease P retention. Applied Agrosilcould increase weight and amount of class A tuber(> 100 g/tuber) with the best dosage 1500 kgSiO2/ha at S2 treatment. This research useful to solve the problem phosphate available in Andisolsoil.Keywords: Chemical Characteristics of Andisols, Agrosil and Phosphorus Fertilizer, Yield ofPotato(Solanum tuberosum L.).